Economic Growth, Comparative Advantage, and Gender Differences in Schooling Outcomes: Evidence from the Birthweight Differences of Chinese Twins - Mark R. Rosenzweig; Junsen Zhang (Asian Development Bank (ADB), 2012)
This paper estimates the gender-specific effects of birthweight on a variety of schooling and labor market outcomes. A unique feature of the study is to use micro evidence on the relationship between birthweight - an early measure of nutritional advantage - and schooling outcomes to make inferences about the relationships between specific aspects of economic growth and schooling investments and returns. Using data from two surveys of twins in the People's Republic of China and applying a simple model of schooling and occupational choice that incorporates differences in brawn between males and females, it shows that the comparative advantage of females in skill is reflected in their greater investment in education and in their selection of more skill-intensive occupations relative to males. It also shows that comparative advantage in skill is manifested in differences in the relationship between birthweight and schooling between males and females, which in turn reflect changes in the skill intensity of the occupational structure in the aggregate economy.
hdl:11540/1262
Keywords: I20; J16; J24; J31; 330; Education; human capital; gender; productivity; wages; twins; PRC; occupational choice; nutrition; birthweight; skills; Bildungsverhalten; Bildungsniveau; Berufswahl; Geschlecht; Humankapital; Arbeitsproduktivität; Wirtschaftswachstum; China